28.1: Distinguished Student Paper: High Performance Fringe‐Field Switching with a Negative Dielectric Anisotropy Liquid Crystal. Issue 1 (1st July 2013) - Chen, Yuan; Luo, Zhenyue; Peng, Fenglin; Wu, Shin‐Tson
Abstract Using our new negative Δε LC material in a fringing field switching (n‐FFS) cell, we demonstrated superior performances to conventional positive ΔεFFS (p‐FFS) LCD in transmittance, viewing angle, cell gap sensitivity, gamma curve, while keeping a comparable operation voltage and response time. Therefore, n‐FFS has potential to replace p‐FFS for next‐generation mobile displays.